1999
DOI: 10.3168/jds.s0022-0302(99)75455-x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrolytic Enzyme Supplements for Dairy Cows in Early Lactation

Abstract: Twenty multiparous lactating Holstein cows in early lactation were used to investigate effects of exogenous fibrolytic enzyme supplementation on dry matter intake, milk production, and digestibility. Cows were blocked according to parity, expected calving date, and milk yield in the previous lactation, and then randomly assigned after calving to two treatments: control or enzyme. The enzyme mixture, which contained mainly xylanase and cellulase activities (Pro-Mote, Biovance Technol. Inc., Omaha, NE), was adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
148
3
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 229 publications
(184 citation statements)
references
References 10 publications
17
148
3
16
Order By: Relevance
“…Loss of BW was greater in Lacaune than in Manchega ewes (35%; P , 0.01) as a consequence of their greater milk yield with similar DM intake and maintenance requirements. Rode et al (1999) observed an increase in milk yield (10%) in dairy cows after adding the (Jarrige, 1989) by using the PreValim 2.7 software. Stage of lactation (week) DM intake (kg/day) Figure 1 Dry matter intake of dairy ewes during the suckling period according to breed and dietary treatment.…”
Section: Resultsmentioning
confidence: 98%
“…Loss of BW was greater in Lacaune than in Manchega ewes (35%; P , 0.01) as a consequence of their greater milk yield with similar DM intake and maintenance requirements. Rode et al (1999) observed an increase in milk yield (10%) in dairy cows after adding the (Jarrige, 1989) by using the PreValim 2.7 software. Stage of lactation (week) DM intake (kg/day) Figure 1 Dry matter intake of dairy ewes during the suckling period according to breed and dietary treatment.…”
Section: Resultsmentioning
confidence: 98%
“…Total N was quantified by flash combustion and thermal conductivity detection (Carlo Erba Instruments, Milan, Italy). Starch concentration was determined by enzymatic hydrolysis of α-linked glucose polymers by the method of Rode et al (1999) with the following modifications. Tubes containing samples were initially incubated in a water bath at 90°C and vortexed at 10, 20 and 30 min of incubation without the use of activated carbon.…”
Section: Measurementsmentioning
confidence: 99%
“…For the measurement of starch and CP (nitrogen (N) × 6.25; AOAC, 1995, method 990.03), samples were ground using a ball mill (Mixer Mill MM 2000; Retsch, Haan, Germany) to a fine powder. Starch was determined by enzymatic hydrolysis of α-linked glucose polymers as described by Rode et al (1999). Total N was determined by flash combustion and thermal conductivity detection (model 1500; Carlo Erba Instruments, Milan, Italy).…”
Section: Animal and Dietsmentioning
confidence: 99%